Расселение американской норки — Mustela (Muslela) vison Sсhr. по Сахалинской области - Беньковский, Л.М. (Вестник зоологии, 1971)
Mustela (Mustela) vison S с h r. inhabiting Sakhalin is considered. The animals
escaping from the farms initiated the wild population of this species on Sakhalin as well
a s on the. island Urup. From 1956 till 1970 564 individuals were delivered from the
Khabarovsk and Altai regions and 198 individuals of Poronaiskian population were simultaneously settled. Now the animals inhabit to the south 50°N.L. , in the Rubnovskian
district and on the island Urup. Ecological conditions for M. vison are not favourable,
that is why the growth of quantity and its further migration over the Sakhalin lands is
not observed. M. vison is an enemy of salmon fry. birds, muskra t and M. (kolonocus)
itatsi T.